Associations between out-of-home care and mental health disorders within and across generations in a Swedish birth cohort - Viviane S. Straatmann; Josephine Jackisch; Lars Brännström; Ylva B. Almquist (Elsevier, 2022)
Previous studies have shown that mental health disorders (MHD) among parents might be an important mechanism in the intergenerational transmission of out-of-home care (OHC). The current study aimed to further study this interplay by investigating the associations between OHC and MHD within and across generations. We used prospective data from the Stockholm Birth Cohort Multigenerational Study (SBC Multigen) on 9033 cohort members (Generation 1; G1) and their 15,305 sons and daughters (Generation 2; G2). By odds ratios of generalised structural equation modelling, we investigated the intergenerational transmission of OHC and MHD, respectively, as well as the association between OHC and MHD within each generation. Second, we examined the associations between OHC and MHD across the two generations. In order to explore possible sex differences, we performed the analyses stratified by the sex of G2. The results showed an intergenerational transmission of OHC, irrespective of sex. Regarding the intergenerational transmission of MHD, it was shown for both sexes although only statistically significant among G2 males. OHC was associated with MHD within both generations; in G2, this association was stronger among the males. While we found no direct association between OHC in G1 and MHD in G2, there was a significant association between MHD in G1 and OHC in G2. The latter was more evident among G2 females than G2 males. We conclude that OHC and MHD seem to be processes intertwined both within and across generations, with some variation according to sex. Although there did not seem to be any direct influences of OHC in one generation on MHD in the next generation, there was some indication of indirect paths going via parental MHD and child OHC.